FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR - Natanael Marcellino; Susanto salim (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to examine the relationship of Managerial Ownership, Institusional Ownership, Risk Litigation, Debt Covenant, and Political Cost to Accounting Conservatism. The objective is to analyze the direction and influence between Managerial Ownership, Institusional Ownership, Risk Litigation, Debt Covenant, and Political Cost to Accounting Conservatism. This study uses a manufacturing industry listed on IDX during 2017-2019 as a population. Sample was selected using purposive sampling method and the valid data was 51 companies. In this research data processing using Microsoft Excel and program Econometrics Views (Eviews10). The result of this study indicate that the impact of institusional ownership, risk litigation and political cost on accounting conservatism is significant. While, managerial ownership, and debt covenant show no significant effect on earnings quality.The implication of this study is the need to expand the sample of companies being used, increase the year of research, and also add more to the independent variables used in the study in order to increase accounting conservatism.